SEGURANÇA E SAÚDE MENTAL DO TRABALHADOR: UM ENFOQUE PSICODINÂMICO DO SOFRIMENTO PSÍQUICO (Estudo de Caso com Operadores e Controladores de Tráfego da Ponte Rio-Niterói) - Lima, Jamaci de Almeida Machado Correa (2008)
The objective of this project was to research data on the health and safety of workers, focusing on the question of mental health and subjectivity in the relationship of the worker to his or her job. The study used theoretical-practical research on a case study a group made up of workers and traffic controllers on the Rio-Niterói bridge. The possibility of existence of mental suffering of the group within a psychodynamic vision was investigated. The methodology included various areas of Knowledge in a interdisciplinary and transdisciplinary approach